Subsídios para implantação de um Núcleo de Apoio à Saúde da Família (NASF) com inserção do médico veterinário - Begali, José Honorato [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The Support Nucleous to Family Health (NASF) was created to expand the coverage and the scope of the Primary Care actions and to increase its resolution. Made up of professionals from different areas of knowledge, it must act interactively, supporting the professional from the Family Health Strategy Team (ESF) and sharing the practices and knowledge about health in the areas under their responsability. The veterinarian can be part of the NASF team, but there are few towns which included this professional, as well as the amount of NASF units in Brazil. This thesis was thought in order to provide subsidies for the proposal of a NASF deployment with the insertion of this professional, using as a basis for study the city of Machado/MG. The main demands in health were checked through a check-list to the community health agents (ACS), nurses and nurse assistants from the ESF teams and the evaluation of the number of cats and dogs as well as their reproductive profile. Two questionnaires were developed and applied for the analysis of the population and the ACS’s perception about zoonosis, especially rabies, the analysis of the ESF health professionals’ perception about the Primary Care Structure, the veterinarian role in the Public Health in both moments of the research. The main detected demands in human health were diabetes, hypertension, obesity, sexually transmitted diseases, alcoholism, drugs use, early pregnancy and accumulators. Regarding the environmental and animals related conditions, we can point out the accumulation of trash, breeding spots of mosquitos, the presence of cats and dogs on the streets, as well as synanthropic animals, mainly doves, rats and ticks, and agressions caused by dogs or cats. The canine and feline population was also estimated in 10.300 animals, from which only 5% are castrated. The questionnaires analysis show that the population and the ACS know little about the veterinarian activities in the Public Health. The Health professionals have a better perception, but not satisfactory, and the problems in the human and animal health interfaces in the environmental context are varied. Therefore, it’s intended to create a NASF Team Modality 1, with a veterinarian included in it, taking part directly to the sanitary measures, which are essential for the Primary Care, inside the paradigm “One world, one health”.

O Núcleo de Apoio à Saúde da Família (NASF) foi criado para ampliar a abrangência e o escopo das ações da Atenção Básica e aumentar sua resolubilidade. Composto por profissionais de diferentes áreas de conhecimento, este deve atuar de maneira integrada apoiando os profissionais das equipes de Estratégia Saúde da Família (ESF) e compartilhando as práticas e saberes em saúde nos territórios sob sua responsabilidade. O médico veterinário pode compor a equipe do NASF, mas ainda são poucos os municípios que incluíram esse profissional, assim como a quantidade de NASF’s no Brasil. Este trabalho foi idealizado com o objetivo de oferecer subsídios para a proposta de implantação de um NASF com inserção deste profissional utilizando como base de estudo o Município de Machado/MG. Foram verificadas as principais demandas em saúde por meio de aplicação de um check-list aos agentes comunitários de saúde (ACS), enfermeiros e auxiliares de enfermagem das equipes de ESF e avaliação do número de cães e gatos e seu perfil reprodutivo; dois questionários foram desenvolvidos e aplicados para análise da percepção da população e dos ACS sobre zoonoses, em especial a raiva, análise da percepção dos profissionais de saúde atuantes na ESF sobre a estrutura da Atenção Básica, e percepção sobre o papel do médico veterinário na saúde pública, em ambos os momentos da pesquisa. As principais demandas em saúde humana detectadas foram diabetes, hipertensão, obesidade, doenças sexualmente transmissíveis, alcoolismo, uso de drogas, gravidez precoce e acumuladores. Quanto às condições ambientais e as que envolvem animais destacam-se acúmulo de lixo, criadouros de mosquitos, presença cães e gatos nas ruas, presença de animais sinantrópicos, principalmente pombos, ratos e carrapatos, e agressões por cão ou gato. Também foi estimada a população canina/felina em 10.300 animais; apenas 5% são castrados. A análise dos questionários mostra que as pessoas e os ACS conhecem pouco sobre as atividades do médico veterinário na Saúde Pública; os profissionais de saúde têm uma percepção melhor, mas não satisfatória; e os problemas nas interfaces da saúde humana e animal no contexto ambiental, são variados. Portanto, propõe-se a criação de uma equipe de NASF modalidade 1 com um médico veterinário inserido na equipe participando diretamente das ações sanitárias, as quais são fundamentais para efetivar a Atenção Básica, dentro do paradigma “Um mundo, uma Saúde”.
Subsidies for deployment of one family health support center (NASF) with veterinary doctor insertion
Keywords: Atenção Básica; ESF; Médico veterinário; NASF; Zoonoses; Primary care; Veterinarian; Zoonosis